의사소통 장애요인이 환자만족도와 장기적 관계지향성에 미치는 영향 - 한다솜(Da-Som Han); 임순연(Soon-Ryun Lim) (한국콘텐츠학회 논문지, 17(2), 2017)
The purpose of this study is to investigate how the communication barriers which patients have at the dental clinic affect the patient's satisfaction and long term sustainable relationship. The subjects of this study were 214 patients from the dental clinic and the analysis was conducted using PASW Statistics 18.0 and IBM SPSS AMOS 21. As the results of factor analysis, the communication barriers were divided to four factors: one-sided communication, lack of trust and concern, patient and environment. In conclusion, the results of this study showed that the communication barriers which patients have with hygienist affected the patient's satisfaction and long term sustainable relationship. So It is imperative that the hygienist makes a concerted effort to ensure the comfort and trust of their patients. In cases where a patient shows discomfort or dissatisfaction, it is important that the hygienist guarantees open communication to the patient in order to gain their trust. Failing to do so may result in difficulties when trying to build a strong client base. 본 연구의 목적은 환자가 경험하는 의사소통 장애가 환자 만족도와 장기적 관계지향성에 미치는 영향을 알아보는데 있다. 치과 병 의원을 방문한 환자 214명을 대상으로 설문조사를 실시하였다. 분석은 PASW Statistics 18.0과 IBM SPSS AMOS 21을 이용하였다. 의사소통 장애 요인분석결과 '일방적소통', '신뢰배려부족', '환자영역', '환경영역'의 요인으로 나뉘었다. 분석 결과, 환자가 느끼는 의사소통 장애요인은 환자 만족도와 장기적 관계지향성에 영향을 미치며, 환자 만족도는 장기적 관계지향성에 영향을 미치는 것으로 나타났다. 이 같은 결과를 바탕으로 치과종사자는 환자와 신뢰를 구축할 수 있는 의사소통 능력을 지니는 동시에 환자 만족도를 높여 계속적인 관계를 유지할 수 있도록 해야 한다.